MIDWIFERY CARE MANAGEMENT FOR 20-YEAR-OLD MRS. P, G1P0A0 GRAVIDA, 40 WEEKS IN PARTU, 1ST STAGE, ACTIVE PHASE WITH PREMATURE RUPTURE OF MEMBRANES AT THE TUTUN SEHATI PRATAMA CLINIC IN 2025 - Sirait, Christina; Putri Ariaty Situmorang; Salsabila Nasywa; almiah; Dewi Sartika Hutabarat; Rohanita Manik, (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Premature rupture of membranes (PROM) in the Medan region varies between 6% and 19% of all pregnancies. Meanwhile, the national rate according to the Ministry of Health and Riskesdas ranges from 5.6% to 14.6%. The expected incidence of PROM in Indonesia is targeted to be significantly reduced to below 5% in order to prevent complications. This case report aims to describe the management of midwifery care for a pregnant woman with premature rupture of membranes and to support the achievement of the Sustainable Development Goals (SDGs) 2030, particularly Goal 3: Good Health and Well-being. The method used was a descriptive case report through a systematic midwifery care approach including assessment, diagnosis, planning, implementation, and evaluation. The case involved Mrs. P, a 20-year-old primigravida (G1P0A0) at 40 weeks of gestation with a single live intrauterine fetus in cephalic presentation and diagnosed with premature rupture of membranes during the active phase of the first stage of labor. The assessment results showed clear amniotic fluid discharge,cervical dilation of 1 cm, fetal heart rate of 156 beats/minute, and stable maternal vital signs. The management provided included monitoring maternal and fetal conditions, preventing infection,emotional support, collaborating with healthcare providers, and administering antibiotics. The mother delivered a baby girl spontaneously with a birth weight of 3100 grams and an Apgar score of 8. The implementation of comprehensive and continuous midwifery care successfully maintained maternal and newborn health and reduced the risk of complications. Early detection and appropriate management of PROM contribute to improving maternal and neonatal outcomes and support the achievement of SDGs 2030 targets in maternal and child health.